Unilateral comminuted and complicated fracture of the mandible due to dog attack - Ngeow, Wei Cheong; Lian, C.B. (1996)
Fractures of the mandible and their management are discussed in detail in textbooks and articles dealing with facial trauma. This paper presents the management and treatment of a case of a unilateral comminuted and complicated fracture of the mandible due to dog attack on a geriatric patient. The attack also severed the patient's right arm. Due to the severity of the trauma, an emergency surgery was performed on the mandible and arm.